2015
DOI: 10.1126/scitranslmed.aad3231
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of GVHD reveals aurora kinase A as a targetable pathway for disease prevention

Abstract: Graft versus host disease (GVHD) is the most common complication of hematopoietic stem cell transplant (HCT). However, our understanding of the molecular pathways that cause this disease remains incomplete, leading to inadequate treatment strategies. To address this, we measured the gene expression profile of non-human primate (NHP) T cells during acute GVHD. Utilizing microarray technology, we measured the expression profiles of CD3+ T cells from five cohorts: allogeneic transplant recipients receiving 1) no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 87 publications
9
83
0
Order By: Relevance
“…In accordance with our previously published results, 6 visualization of the top 25 gene sets in the hyperacute cohort using constellation mapping 10,11 revealed that proliferative signals were a dominant theme in the T-cell transcriptional profile of hyperacute GVHD ( Figure 3C), with 21 of 25 top correlating gene sets describing proliferative programing, and 15 of these demonstrating significant sharing of enriched transcripts (depicted as red circles in Figure 3C). Similar to our previous work, GSEA revealed that Th/Tc1 transcripts were overrepresented in animals with hyperacute GVHD compared with T cells purified from both healthy controls, and from recipients with breakthrough acute GVHD 12 ( Figure 3D).…”
Section: Transcriptomics Distinguish Hyperacute and Breakthrough Acutsupporting
confidence: 69%
See 2 more Smart Citations
“…In accordance with our previously published results, 6 visualization of the top 25 gene sets in the hyperacute cohort using constellation mapping 10,11 revealed that proliferative signals were a dominant theme in the T-cell transcriptional profile of hyperacute GVHD ( Figure 3C), with 21 of 25 top correlating gene sets describing proliferative programing, and 15 of these demonstrating significant sharing of enriched transcripts (depicted as red circles in Figure 3C). Similar to our previous work, GSEA revealed that Th/Tc1 transcripts were overrepresented in animals with hyperacute GVHD compared with T cells purified from both healthy controls, and from recipients with breakthrough acute GVHD 12 ( Figure 3D).…”
Section: Transcriptomics Distinguish Hyperacute and Breakthrough Acutsupporting
confidence: 69%
“…We have previously reported the flow cytometric 4 and transcriptional attributes 6 of T cells causing GVHD in the absence of immunosuppression ("No Rx"). These attributes include a highly proliferative T-cell program, characterized by multiple markers of Th/Tc1 skewing and expression of granzymes and interferon g (IFNg).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This work has been driven by detailed flow cytometric evaluation of the T-and B-cell subpopulations driving both acute and chronic disease, [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102] as well as increasing use of systems-based transcriptomic approaches to identifying the pathways associated with GVHD, both in preclinical models and clinical samples. 50, [103][104][105][106][107] This work is identifying a new cohort of targetable pathways for GVHD control, many of which are amenable for clinical translation.…”
Section: Postneutrophil Engraftmentmentioning
confidence: 99%
“…In experimental murine GVHD inhibition of the aurora A kinase pathway with a commercially available selective, reversible small-molecule inhibitor (MLN8237, alisertib) mitigated clinical severity and improved survival. [143] Human clinical trials have not yet been conducted.…”
Section: Emerging Therapiesmentioning
confidence: 99%